On‐court game‐based testing in world‐class, top‐elite, and elite adult female team handball players. Issue 3 (10th February 2020) - Wagner, Herbert; Fuchs, Patrick; Michalsik, Lars Bojsen
Abstract: The on‐court physical performance knowledge of adult female world‐class players in team handball is lacking, especially when testing specific physical performance on‐court under similar conditions as in competition. Consequently, the aims of the study were to analyze team handball on‐court physical performance in elite, top‐elite, and world‐class female team handball players by using team handball specific testing. Ten elite, eleven top‐elite, and eleven world‐class adult female players performed a team handball game‐based performance test. We measured oxygen uptake, heart rate, blood lactate concentration, ball velocity, and jump height in the jump shots as well as running time (in offense, defense, fast break, and retreat). Significant differences were found in peak oxygen uptake, heart rate, ball velocity, defense, offense, and fast‐break time between world‐class, top‐elite, and elite players. During breaks, between the high‐intensity movements in the game‐based performance test, a world‐class player had greater increase in oxygen uptake compared with an elite player. The results of the present study clearly indicated the importance of specific agility both in offense and defense, in throwing velocity in the jump shot as well as in aerobic performance to become a world‐class adult female team handball player.